Pengaruh Iklim Organisasi Dan Kepuasan Kerja Terhadap Kinerja Karyawan - Renaldi, Refli; Khaira, Imamul (Jurusan Akuntansi Politeknik Negeri Padang, 2021)
This study is to examine the influence: between atmosphere of the organization and employees’ satisfaction against the employees’ performance partially or simultaneously. The good atmosphere of the organization became more effective in increasing employees’ work satisfaction; and finally obtain good employees’ performance. This situation cannot be found in this company. This study used descriptive methode. All of employees became sample (36 people). The data was collected by observation, interview and questioner. The data were analyzed by using multiple regression analysis with F-test (simultaneous) and T-test (partial) at the significance level of 95%. The result of the study provides a conclusion as follow: 1. There is a significant influence between organization atmosphere against the employees’ performance in PT. Yuri Cakra Brothers. (2) There is a significant influence between employees’ satisfaction against the employees’ performance in PT. Yuri Cakra Brothers, (3) There is a significant influence between organization atmosphere and employees’ satisfaction altogether against employees’ performance in PT. Yuri Cakra Brothers.